Body and milk quality traits of purebred Holstein and three-generation crossbred cows from Viking Red, Montbéliarde, and Holstein sires - Sudeb Saha (Journal of Central European Agriculture, 2018)
The objective of this study was to investigate the effects of 3-way rotational crossbreeding scheme of Holstein (HO) cows with Montbéliarde (MO), Viking Red (VR) and HO sires on body and milk quality traits. Cows were purebred HO; F1: (MO × HO; VR × HO); F2: [MO × (VR × HO); VR × (MO × HO)]; F3: {HO × [MO × (VR × HO)]}; HO × [VR x (MO × HO)]}. Data were collected on 745 cows kept in a commercial farm located in Northern Italy. Milk data were acquired from official milk recording and body condition score (BCS) and conformation traits were measured once by trained evaluator. Data were analyzed using a linear model including fixed effects of parity, DIM class and breed combinations. Average body traits: height at withers (HW), body length (BL) and heart girth (HG) of cows were 139,162 and 207 cm respectively. Crossbred cows had shorter HW, BL and HG than pure HO but greater BCS. Milk yield averaged 31.5 kg/d, with fat and protein content close to 3.8 and 3.75%, respectively. Purebred HO produced greater volume of milk than crossbreds but milk from HO had lower protein content. Different combinations of crossbred cows showed similar performance in terms of milk yield traits, but evidenced different body size. The trial is currently in progress to increase cow sample size and widen the number of herds involved.